The association between HIV/AIDS and childhood sexual abuse: An exploratory case study. Issue 4 (2nd October 2019) - Diao, Xavier Y.; Albert, Madeline; Forstein, Marshall
Abstract: The effects of sexual abuse in childhood are serious and far-reaching, and include a number of short- and long-term sequelae, including depression, anxiety, disordered eating, post-traumatic stress disorder (PTSD), substance abuse disorders, suicidal ideation and self-injurious behavior, sexual dysfunction, borderline personality traits, high-risk sexual behavior, and dissociative disorders. MSM (men who have sex with men) with a history of childhood sexual abuse are more likely to engage in high-risk sexual behavior, trade sex for substances and/or money, experience intimate partner violence, and report as being HIV-positive. In this case study, we aim to explore the association between sexual abuse in childhood and HIV/AIDS. We identify a HIV-positive gay man with a history of sexual abuse and review the existing literature on the subject of HIV and sexual abuse, with a focus on victims who are MSM. Early childhood traumas, especially sexual abuse, can have immense and long-lasting psychological sequelae. Here, we report a victim of childhood sexual abuse who suffers from PTSD, selective amnesia, and episodes of dissociation during sex who was diagnosed as being HIV-positive at the height of the HIV/AIDS epidemic in the United States. More research needs to be done to investigate the complex relationship between childhood trauma and HIV infection, with insights into racial, gender, and socioeconomic differences. Counseling and risk-reduction strategies need to be explored with patients with a history of sexual trauma, in tandem with long-term pharmacologic and therapeutic interventions.